Analisis Perbandingan Kinerja Keuangan Bank Umum Syariah BUMN dan Non BUMN dengan Metode RGEC - Hafiz Santak Taram; Isfandayani Isfandayani (LPPM Universitas Islam 45, 2022)
This study aims to analyze the comparison of the financial performance of BUMN Islamic commercial banks and BUMN Non Islamic commercial banks on the variables of Risk Profile, Good Corporate Governance, Earnings, and Capital (RGEC) for the 2017-2020 period represented by the ratio of Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Operating Expenses to Operating Income (BOPO), Good Corporate Governance (GCG), Return On Assets (ROA), Return On Equity (ROE), and Capital Adequacy Ratio (CAR). The results of this study show that of the 7 ratios analyzed, there are 5 ratios with significant differences between the financial performance of BUMN Islamic commercial banks and Non BUMN Islamic commercial banks during the 2017-2020 period, namely FDR with a significance of 0.000, BOPO with a significance of 0.011 Good Corporate Governance with a significance of 0.011. 0.003 significance, ROA with 0.024 significance, and ROE with 0.020 significance. While the NPF ratio with a significance of 0.921, CAR with a significance of 0.744, and RGEC Composite Rating with a significance of 0.510 there is no significant difference between the financial performance of BUMN Islamic commercial banks and non-BUMN Islamic commercial banks during the 2017-2020 period. The last analysis on the consolidated financial performance assessment of all RGEC variables shows that the performance of BUMN Islamic commercial banks is not better than the performance of Non-BUMN Islamic commercial banks where the average composite value for 4 years is the performance of BUMN Islamic commercial banks (80%).